Investigation of the psychometric properties of the Comprehensive Feeding Practices Questionnaire in Turkish parents - Ceren Şarahman-Kahraman; Cansu Memiç-İnan; Nurcan Yabanci-Ayhan; Ayse Özfer Ozcelik (Cambridge University Press, 2024)
Abstract Objective: The Comprehensive Feeding Practices Questionnaire (CFPQ) measures parental attitudes towards feeding practices that directly influence children's eating habits. This study aims to determine the reliability and validity of the Turkish adaptation of the CFPQ developed by Musher-Eizenman et al. Design: Validity and reliability analyses were conducted for the Turkish version of the CFPQ (T-CFPQ). In addition to reliability analyses and partial correlations between scale dimensions, correlations between scale dimensions according to mothers' BMI and children's BMI z-scores were also examined. Setting: Parents with children aged 18 months to 8 years living in the community. Participants: The study sample consisted of 274 parents with children aged 18 months to 8 years who agreed to participate in the online survey. Results: In this study, forty-seven items and twelve-factor structure describing feeding practices were supported by the confirmatory factor analysis. Although most of the dimensions of the T-CFPQ showed significant correlations with each other, the highest correlation was found between the encourage balance/variety and the dimension of modelling and teaching nutrition (r = 0·53; 0·50) (P < 0·05). There was a negative correlation between the child's BMI z-score and the pressure to eat dimension (r = -0·173; P < 0·01) and a positive correlation between the restriction for weight dimension (r = 0·339; P < 0·01). Maternal BMI was negatively associated with the involvement dimension (r = -0·121; P < 0·05) and positively associated with the restriction for weight dimension (r = 0·154; P < 0·01). Conclusions: The findings revealed that the T-CFPQ is a valid and reliable measurement tool that can be applied to obtain the necessary information for evaluating nutritional interactions between parent and child.